The Roles of Intuition and Informants' Expertise in Children's Epistemic Trust. Issue 3 (26th November 2014) - Lane, Jonathan D.; Harris, Paul L.
<x xml:space="preserve">Abstract</x> This study examined how children's intuitions and informants' expertise influence children's trust in informants' claims. Three‐ to 8‐year‐olds (N = 192) watched videos in which experts (animal/biology experts or artifact/physics experts) made either intuitively plausible or counterintuitive claims about obscure animals or artifacts. Claims fell either within or beyond experts' domains of expertise. Children of all ages were more trusting of claims made by informants with relevant, as opposed to irrelevant, expertise. Children also showed greater acceptance of intuitive rather than counterintuitive claims, a differentiation that increased with age as they developed firmer intuitions about what can ordinarily happen. In summary, children's trust in testimony depends on whether informants have the relevant expertise as well as on children's own developing intuitions.